Development of model for large-bore engine cooling systems - Kendrick, Clint Edward (Kansas State University, 2011)
The purpose of this thesis is to present on the development and results of the cooling system logic tree and model developed as part of the Pipeline Research Council International, Inc (PRCI) funded project at the Kansas State National Gas Machinery Laboratory. PRCI noticed that many of the legacy engines utilized in the natural gas transmission industry were plagued by cooling system problems. As such, a need existed to better understand the heat transfer mechanisms from the combusting gases to the cooling water, and then from the cooling water to the environment. To meet this need, a logic tree was developed to provide guidance on how to balance and identify problems within the cooling system and schedule appropriate maintenance. Utilizing information taken from OEM operating guides, a cooling system model was developed to supplement the logic tree in providing further guidance and understanding of cooling system operation. The cooling system model calculates the heat loads experienced within the engine cooling system, the pressures within the system, and the temperatures exiting the cooling equipment. The cooling system engineering model was developed based upon the fluid dynamics, thermodynamics, and heat transfer experienced by the coolant within the system. The inputs of the model are familiar to the operating companies and include the characteristics of the engine and coolant piping system, coolant chemistry, and engine oil system characteristics. Included in the model are the various components that collectively comprise the engine cooling system, including the water cooling pump, aftercooler, surge tank, fin-fan units, and oil cooler. The results of the Excel-based model were then compared to available field data to determine the validity of the model. The cooling system model was then used to conduct a parametric investigation of various operating conditions including part vs. full load and engine speed, turbocharger performance, and changes in ambient conditions. The results of this parametric investigation are summarized as charts and tables that are presented as part of this thesis.
Keywords: Engine cooling system; Heat transfer; Heat exchanger modeling; Piping system modeling; Engine heat transfer; National gas machinery laboratory; Engineering (0537); Mechanical Engineering (0548)